Ribotipos depolymyxa graminis en muestras de arroz y de malezas provenientesde arroceras de Argentina - Solis, Valentina Eva; Gutiérrez, S.A.; Celli, Marcos Giovani (Asociación Argentina de Fitopatólogos (AAF), 2024)
Poster